MACHINE LEARNING PREDICTIVE MODEL DEVELOPMENT FOR VACUUM DISTILLATION UNIT IN LUBRICANT BASE OIL PRODUCTION - SARAVANAN, PRAKASH (2021)
Predictive modelling through machine learning is utilized to accurately determine the predictive variables for a given target variable in the operation of a Vacuum Distillation Unit in a lubricant base oil plant. This is done by training the model using 70% of the past plant data from 2018 to 2020 and enables the model to capture the correlations between the target variables and the predictor variables.